Hubungan Pengetahuan Karies dengan Karies Gigi Molar Pertama Permanen Pada Murid Umur 10-12 Tahun di SDN Kelayan Selatan 10 Kota Banjarmasin - Annisa, Nurul; Rahmawati, Ida; Astu Rahman, Waljuni; Salamah, Siti (Poltekkes Kemenkes Banjarmasin, 2024)
Based on the results of a preliminary study conducted on October 17, 2022 at SDN Kelayan Selatan 10 Kota Banjarmasin. Out of 10 students, 3 students had good knowledge and 7 had less knowledge. Meanwhile, 9 of them had permanent first molar dental caries. The purpose of this study was to determine the relationship between caries knowledge and permanent first molar dental caries in students aged 10-12 years at SDN Kelayan Selatan 10 Kota Banjarmasin. This research type uses Analytical Survey, the research design uses Cross-Sectional and the sampling uses Total Sampling method with a sample size of 60 students. The data were analyzed using the Chi Square test. The research results showed that caries knowledge was mostly in the poor category, and permanent first molar caries was mostly in the caries category. The statistical analysis resulted in a ρ-value of 0.000, indicating a significance level of p < a (0.05). Thus, the null hypothesis (Ho) was rejected, and the alternative hypothesis (Ha) was accepted. In conclusion, there is a relationship between caries knowledge and permanent first molar dental caries in students aged 10-12 years at SDN Kelayan Selatan 10 Kota Banjarmasin. It is suggested that the School and Public Health Center can cooperate in the implementation of dental and oral health care service activities which contain promotive, preventive, and curative activities to increase optimal dental health status.